Diagnóstico de los factores que afectan la demanda de los atractivos turísticos del cantón Quinsaloma - Ortiz Cedeño, Alexander Geovanny (2021)
The search to improve those factors that intervene in the demand for the tourist attractions of the Quinsaloma Canton will be of great help, since, through the diagnosis, they will be known and they will try to apply the improvement strategies to increase the tourist demand in these sectors, In addition, involving the population of the sector will allow its total growth, therefore, these questions will arise; Why? And in what way will it do it? Although it is true that those factors that are involved in the demand of the tourist places of the Quinsaloma Canton will be sought, then, that is when the fundamental axes enter that will benefit the entire population in a general way. , which will be the nature, the social and the economic. Depending on the diagnosis that they implement, the causes of the variables that are affecting will be determined and do not allow the process to be carried out normally and effectively, that is, at the time of identifying these variables they will be analyzed in all aspects and subsequently will teach them for their respective implementation. In addition, it is worth mentioning that the methodology presented in the research was the best to carry it out and obtain favorable results in the face of the problem and that these have a positive action in the general population and its entire environment at the time of applying it.